2023
DOI: 10.7150/ijms.83760
|View full text |Cite
|
Sign up to set email alerts
|

FANCI is Associated with Poor Prognosis and Immune Infiltration in Liver Hepatocellular Carcinoma

Abstract: Objective: This study aimed to validate FANCI as a potential marker for both prognosis and therapy in liver hepatocellular carcinoma. Method: FANCI expression data were acquired from GEPIA, HPA, TCGA, and GEO databases. The impact of clinicopathological features was analyzed by UALCAN. The prognosis of Liver Hepatocellular Carcinoma (LIHC) patients with highly expressed FANCI was constructed utilizing Kaplan-Meier Plotter. GEO2R was employed to identify differentially express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The high FANCI expression level may boost up tumor growth in lung adenocarcinoma by inhibiting M1 macrophages (34, 35). Additionally, FANCI expression in liver hepatocellular carcinoma showed a positive relationship with tumor infiltration levels (36). These results indicated that FANCI may regulate the immune microenvironment of tumors.…”
Section: Discussionmentioning
confidence: 73%
“…The high FANCI expression level may boost up tumor growth in lung adenocarcinoma by inhibiting M1 macrophages (34, 35). Additionally, FANCI expression in liver hepatocellular carcinoma showed a positive relationship with tumor infiltration levels (36). These results indicated that FANCI may regulate the immune microenvironment of tumors.…”
Section: Discussionmentioning
confidence: 73%
“…The expression of NF-κB-p65 (RelA) and TNFα in GBM was utilized to create the overall survival (OS) curves; patients with a high level of expression (>median expression value) and patients with a low level of expression (<median expression value) were defined. The Kaplan-Meier (KM) method was used to evaluate overall survival using a log-rank test (statistically significant: p-value < 0.05) and to determine the hazards ratio (HR) with a 95% confidence interval [19]. In order to validate patient survival statistics, through UALCAN, we also ascertained the amounts of NF-κB p65 (RelA) and TNFα gene expression in GBM and also determined the functionality of genes that affected the patients' survival times.…”
Section: Bioinformatics Analysismentioning
confidence: 99%